Dekke Na Niarsik: Identitas Budaya Etnis Batak Toba di Pematangsiantar - Siahaan, Giovanni Minar Gabriella; Aliffiati, .; Murniasih, A.A.A. (Sunari Penjor : Journal of Anthropology, 2023)
The Batak Toba tribe has a very important traditional food for its people, namely dekke na niarsik. Dekke na niarsik is one of the traditional foods made from carp that is used in various traditional events of the Batak Toba tribe. Along with the development of the times, dekke na niarsik remains and continues to be consumed by the Batak Toba people, especially in Pematangsiantar City. The main problem of this research focused on the dekke na niarsik which is the cultural identity of the Batak Toba in Pematangsiantar city and the functions contained in the dekke na niarsik for the Batak Toba people in Pematangsiantar city. This research used the theory of the function of food by Foster and Anderson, and the theory of cultural identity by Myron Lustig. The findings of the research reveal that dekke na niarsik is a cultural heritage of the Batak Toba people in the form of culinary offerings. Dekke is award an odd number of times on each anniversary or event. Dekke na niarsik is given at the time of marriage, birth, seven months, adopting sidi, graduating from college, until the death ceremony. There for dekke na niarsik symbolizes the life cycle of the Batak Toba people from birth to the end of their lives.